Solar-based green hydrogen production for decarbonizing natural gas: An emissions perspective - Sahin, Habip (Pergamon-Elsevier Science Ltd, 2026)
The integration of green hydrogen into natural gas networks represents a practical strategy for reducing carbon emissions in fossil fuel-dependent energy systems. This study investigates the potential of solar-powered electrolysis for green hydrogen production and its subsequent blending with natural gas as a transitional decarbonization approach. A 200 kW PEM electrolyzer model, powered by solar energy, was developed using hourly irradiance data for I(center dot)zmir, T & uuml;rkiye. Hydrogen blends at 5 %, 10 %, and 20 % by volume were evaluated in terms of energy content, density, and equivalent CO2 emissions. The system achieved a specific energy consumption of 59.18 kWh/kgH2, producing an average of 21.8 kg/day and a total of 7939.2 kg annually, with a corresponding levelized cost of hydrogen of $5.29/kgH2. Environmental analysis showed that hydrogen injection could prevent up to 84.6 metric tons of equivalent CO2 emissions. Even with isothermal energy correction, net emission reductions of 1.62 %, 3.36 %, and 7.25 % were observed. The findings confirm that small-scale solar-based hydrogen systems can meaningfully support near-term decarbonization targets.
Keywords: Electrolysis; Emission mitigation; Green hydrogen; Hydrogen-enriched natural gas; Renewable energy